Щодо деяких шляхів підвищення ефективності індивідуального запобігання злочинам в Україні - Кондратішина, В.; Kondratishyna, V. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуті питання, що стосуються змісту діяльності неспеціалізованих суб’єктів, зокрема адвокатури, щодо індивідуального запобігання злочинам в Україні, визначені основні проблемні моменти та сформульовані науково обґрунтовані заходи стосовно їх вирішення по суті.During the implementation of the individual measures aimed at preventing crime attorneys must adhere to the basic requirements to this type of social activity. The author claims that these measures must be concrete and practically reasonable, legal and socially just, democratic and transparent, comprehensive and systematic, scientifically justified, humane, realistic and economical. The author differentiates the objects of the individual prevention of crime, usually exercised by a lawyer: 1) behavior and lifestyle of the clients with a high probability of committing a crime; 2) social characteristics of a personality that reflect criminal’s antisocial orientation; 3) lack of socially important psychophysical characteristics of an individual that determine his social behavior; 4) unfavorable surrounding such as environment conditions and person’s mode of life; 5) other long-term lasting circumstances that define criminal situation and facilitate the commitment of a crime by a client of the lawyer, who protects the legitimate rights and interests of the latter.
Some Ways to Raise Efficiency of the Individual Prevention of Crime in Ukraine
Keywords: злочин; запобігання; суб’єкти запобігання злочинам; індивідуальне запобігання злочинам; ефективність; діяльність; система; адвокатура; crime; prevention; subjects of crime prevention; individual crime prevention; efficiency; activity; system; advocacy